IMPACT-Scot 2 report on COVID-19 in hip fracture patients: a nationwide study of mortality, risk factors for community and hospital acquired COVID-19, and suggested care pathways. (3rd May 2021) - Hall, Andrew J.; Clement, Nick D.; ,; MacLullich, Alasdair M. J.; White, Tim O.; Duckworth, Andrew D.
Abstract : Aims: The primary aim was to determine the influence of COVID-19 on 30-day mortality following hip fracture. Secondary aims were to determine predictors of COVID-19 status on presentation and later in the admission; the rate of hospital acquired COVID-19; and the predictive value of negative swabs on admission. Methods: A nationwide multicentre retrospective cohort study was conducted of all patients presenting with a hip fracture to 17 Scottish centres in March and April 2020. Demographics, presentation blood tests, COVID-19 status, Nottingham Hip Fracture Score, management, length of stay, and 30-day mortality were recorded. Results: In all, 78/833 (9.4%) patients were diagnosed with COVID-19. The 30-day survival of patients with COVID-19 was significantly lower than for those without (65.4% vs 91%; p < 0.001). Diagnosis of COVID-19 within seven days of admission (likely community acquired) was independently associated with male sex (odds ratio (OR) 2.34, p = 0.040, confidence interval (CI) 1.04 to 5.25) and symptoms of COVID-19 (OR 15.56, CI 6.61 to 36.60, p < 0.001). Diagnosis of COVID-19 made between seven and 30 days of admission to hospital (likely hospital acquired) was independently associated with male sex (OR 1.73, CI 1.05 to 2.87, p = 0.032), Nottingham Hip Fracture Score ≥ 7 (OR 1.91, CI 1.09 to 3.34, p = 0.024), pulmonary disease (OR 1.68, CI 1.00 to 2.81, p = 0.049), American Society of Anesthesiologists (ASA) grade ≥ 3 (OR 2.37, CI 1.13 to 4.97, p = 0.022), and length of stay ≥ nine days (OR 1.98, CI 1.18 to 3.31, p = 0.009). A total of 38 (58.5%) COVID-19 cases were probably hospital acquired infections. The false-negative rate of a negative swab on admission was 0% in asymptomatic patients and 2.9% in symptomatic patients. Conclusion: COVID-19 was independently associated with a three times increased 30-day mortality rate. Nosocomial transmission may have accounted for approximately half of all cases during the first wave of the pandemic. Identification of risk factors for having COVID-19 on admission or acquiring COVID-19 in hospital may guide pathways for isolating or shielding patients respectively. Length of stay was the only modifiable risk factor, which emphasizes the importance of high-quality and timely care in this patient group.